Utilizing Traditional Teaching Methods to Optimize Aqidah Akhlak Learning in Conditions of Limited Resources: A Case Study at MTs Al-Hidayah Cibodas Wanareja - Yahya, Fitria; Mu’afi, Irfan; Sakana, Mufti Fatikhatus; Musyrifah, Farida (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Traditional methods of teaching faith and morals, such as lectures, memorization, sorogan, bandungan, and repetition, remain the mainstay of Islamic education. Although often associated with being outdated, these methods still play an important role in shaping moral and spiritual values, as well as a basic understanding of faith. This study aims to explain the characteristics of traditional methods, how these methods are applied in the teaching of faith and morals, and to evaluate the advantages, disadvantages, and relevance of these methods in the context of education in the 21st century at MTS Al-hidayah Cibodas Wanareja. As a new educational institution with limited facilities and infrastructure, it faces challenges in adopting digital technology. However, these limitations have actually triggered a strengthening of conventional methods. The research was conducted using a descriptive qualitative approach, where data was collected through observation, interviews, and documentation studies. The results of the study indicate that traditional methods are still necessary as a basis for the transfer of knowledge from teachers to students, but they need to be balanced with modern learning approaches to meet the needs of today's students. Traditional methods emphasize emotional and spiritual touch (psychology-pedagogy), which is often reduced in screen-based learning. The effectiveness of character education is not determined by the strength of the interaction between educators and students.